Antiphospholipid antibodies induce endothelial procoagulant activity and release of extracellular vesicles independently of a second hit - Álvarez, Daniel; Winter, Hephzibah E.; Markert, Udo R.; Cadavid J., Ángela P.; Morales-Prieto, Diana M. (Frontiers in Immunology, 2025)
IntroductionAntiphospholipid antibodies (aPLs) can promote thrombosis in vivo, but evidence from both animal models and clinical data suggests that they act as a ‘first hit’ and may require a ‘second hit’, typically an inflammatory stimulus, to induce thrombus formation. This study aimed to investigate whether polyclonal aPLs alone can induce effects in human endothelial cells that are sufficient to trigger ex vivo clot formation and to induce the release of endothelial extracellular vesicles (EVs) carrying an altered cargo.MethodsHuman umbilical vein endothelial cells (HUVECs) were stimulated with IgG from patients with vascular and obstetric APS (IgG APS) or IgG purified from the serum of healthy women with proven gestational success (IgG healthy control —HC—). IgG binding to HUVECs, expression of tissue factor, and the procoagulant activity of the endothelial surface were evaluated. EVs were isolated from the supernatants and characterized by nanoparticle tracking analysis, cryo-transmission electron microscopy, flow cytometry, and Western blotting.ResultsCompared to IgG HC, IgG APS showed increased binding to the endothelial surface upon prior and concomitant stimulus with LPS (HC 10.92; APS 81.61 mean fluorescence intensity —MFI—, p < 0.01). This enhanced binding capacity of IgG APS to HUVECs was preserved even in the absence of LPS (HC 12.23; APS 84.26 MFI, p < 0.05). Additionally, IgG APS enhanced the platelet-rich plasma-dependent procoagulant activity of the endothelial surface (HC 0.031; APS 0.098 clot density; p < 0.05), and the release of large EVs (HC 7.3 x 108; APS 1.1 x 109 particles; p < 0.05). These lEVs were frequently opsonized by IgG (lEVC 28.5; lEVAPS 40.6%, p < 0.001).ConclusionOur findings suggest that IgG APS can trigger second hit-independent procoagulant mechanisms in HUVECs and induce the release of lEVs that subsequently display surface-bound IgG, highlighting a potential role for endothelial EVs in APS pathophysiology.